2022
DOI: 10.3389/fcvm.2022.858594
|View full text |Cite
|
Sign up to set email alerts
|

SS31 Alleviates Pressure Overload-Induced Heart Failure Caused by Sirt3-Mediated Mitochondrial Fusion

Abstract: Heart failure caused by pressure overload is one of the leading causes of heart failure worldwide, but its pathological origin remains poorly understood. It remains critical to discover and find new improvements and treatments for pressure overload-induced heart failure. According to previous studies, mitochondrial dysfunction and myocardial interstitial fibrosis are important mechanisms for the development of heart failure. The oligopeptide Szeto-Schiller Compound 31 (SS31) can specifically interact with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The main advantages of SS peptides over the TPP-like MTAs are that their cellular uptake is energy independent, and their uptake in mitochondria is independent of MMP [ 130 ]. A large body of evidence shows that SS31 treatment reduces ROS production, improves mitochondrial functioning, and prevents mitochondrial structural changes and phospholipid oxidation in different disorders [ 131 , 132 , 133 , 134 ]. SS-31 has also been shown to be safely tolerated and exert protective effects in phase I clinical trials of patients with heart failure [ 135 ] and phase II trials of reperfusion injury patients [ 136 ].…”
Section: Mitochondria-targeted Antioxidants In Copdmentioning
confidence: 99%
“…The main advantages of SS peptides over the TPP-like MTAs are that their cellular uptake is energy independent, and their uptake in mitochondria is independent of MMP [ 130 ]. A large body of evidence shows that SS31 treatment reduces ROS production, improves mitochondrial functioning, and prevents mitochondrial structural changes and phospholipid oxidation in different disorders [ 131 , 132 , 133 , 134 ]. SS-31 has also been shown to be safely tolerated and exert protective effects in phase I clinical trials of patients with heart failure [ 135 ] and phase II trials of reperfusion injury patients [ 136 ].…”
Section: Mitochondria-targeted Antioxidants In Copdmentioning
confidence: 99%
“…Interestingly, in a rat model of hypertension with cardiac insufficiency, promoting glucagon-like peptide-1 (GLP-1) production enhanced mitochondrial fusion in the heart and improved cardiac function ( 161 ). In a recent study, the oligopeptide Szeto-Schiller compound 31 (SS31) was found to significantly improve cardiac function, reduce myocardial interstitial fibrosis, and increase expression of optic atrophy-associated protein 1 (Opa1) in mice with pressure-overload heart failure by modulating mitochondrial fusion ( 162 ).…”
Section: Mitochondrial Dynamics and Target-organ Damage Of Vascular D...mentioning
confidence: 99%